2020
DOI: 10.4103/aja.aja_63_19
|View full text |Cite
|
Sign up to set email alerts
|

A 30-year retrospective study of rare ectopic seminal tract opening cases

Abstract: rare incidence and atypical symptoms of these conditions make clinical diagnosis and treatment difficult. In this study, we retrospectively analyzed 28 such cases, proposed a new classification of ESTO, and applied it in clinical practice to provide valuable references for diagnosis and treatment of the condition. PATIENTS AND METHODS Study population and clinical manifestationsFrom August 1985 to August 2015, 28 cases of ESTO in patients aged 2-48 years old were diagnosed and treated in the First Affiliated H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…In addition, we provide the findings of our literature review of published cases of ectopic openings of EDs (Table 1). We identified 24 such published cases (Khunovich et al, 2020; Lin et al, 2012; Reisman, 1977; Wang et al, 2009; Wu et al, 2020); of which only one reported case was of bilateral ectopic EDs openings in the bladder trigone observed in a 3‐year‐old child (Khunovich et al, 2020). Hence, to our knowledge, our case is the second ever reported of bilateral ectopia of EDs openings in the bladder trigone; and the first observed in an adult associated with primary infertility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we provide the findings of our literature review of published cases of ectopic openings of EDs (Table 1). We identified 24 such published cases (Khunovich et al, 2020; Lin et al, 2012; Reisman, 1977; Wang et al, 2009; Wu et al, 2020); of which only one reported case was of bilateral ectopic EDs openings in the bladder trigone observed in a 3‐year‐old child (Khunovich et al, 2020). Hence, to our knowledge, our case is the second ever reported of bilateral ectopia of EDs openings in the bladder trigone; and the first observed in an adult associated with primary infertility.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the anomaly, the literature review we undertook (Table 1) depicts that ectopic EDs most commonly open in the midline cyst, raising suspicion of an enlarged prostatic utricle (Lin et al, 2012; Wu et al, 2020). In a few rare cases, the ectopic ED invades the bladder trigone, bladder neck and urethra (Reisman, 1977; Wang et al, 2009; Wu et al, 2020). One patient had the ED ending in a large cystic dead‐end, compressing the bladder and the contralateral ED (Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The congenital anomalies of the ductus deferens, which are rare, affect approximately 0.05% of the general population. This phenomenon has two main types, ectopic ejaculatory duct opening, and ectopic vas deferens opening [ 1 ]. In general, Ductus deferens' precise etiology is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The function of testicles is usually impaired and their structure is abnormal, while external genitalia are often ambiguous. Until now only a single causative mutation responsible for Persistent Müllerian Duct Syndrome (PMDS) was identified in dogs(26). The mutation of Müllerian inhibiting substance type II receptor (MISRII) gene occurred in Miniature Schnauzers and was reported in different populations of this breed(12).…”
mentioning
confidence: 99%